A systematic review showing the lack of diagnostic criteria and tools developed for lower‐limb cellulitis. (1st December 2019) - Patel, M.; Lee, S.I.; Akyea, R.K.; Grindlay, D.; Francis, N.; Levell, N.J.; Smart, P.; Kai, J.; Thomas, K.S.
Summary: Background: Cellulitis can be a difficult diagnosis to make. Furthermore, 31% of patients admitted from the emergency department with suspected lower‐limb cellulitis have been misdiagnosed, with incorrect treatment potentially resulting in avoidable hospital admission and the prescription of unnecessary antibiotics. Objectives: We sought to identify diagnostic criteria or tools that have been developed for lower‐limb cellulitis. Methods: We conducted a systematic review using Ovid MEDLINE and Embase databases in May 2018, with the aim of describing diagnostic criteria and tools developed for lower‐limb cellulitis, and we assessed the quality of the studies identified using the Quality Assessment of Diagnostic Accuracy Studies‐2 tool. We included all types of study that described diagnostic criteria or tools. Results: Eight observational studies were included. Five studies examined biochemical markers, two studies assessed imaging and one study developed a diagnostic decision model. All eight studies were considered to have a high risk for bias in at least one domain. The quantity and quality of available data was low and results could not be pooled owing to the heterogeneity of the findings. Conclusions: There is a lack of high‐quality publications describing criteria or tools for diagnosing lower‐limb cellulitis. Future studies using prospective designs, validated in both primary and secondary care settings, are needed. What's already known about this topic? Diagnosing lower‐limb cellulitis on first presentation is challenging. Approximately one in three patients admitted from the emergency department with suspected lower‐limb cellulitis do not have cellulitis and are given another diagnosis on discharge. Consequently, this results in potentially avoidable hospital admissions and the prescription of unnecessary antibiotics. There are no diagnostic criteria available for lower‐limb cellulitis in the U.K. What does this study add? This systematic review has identified a key research gap in the diagnosis of lower‐limb cellulitis. There is a current lack of robustly developed and validated diagnostic criteria or tools for use in clinical practice.